An analysis of female language choices and cultural identity in digital advertisement - Sari, Farnia; Amaliah , Amaliah; Rivani , Falizar; Wahyudi , Agus (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The digital advertisement may affect cultural identity and language choice in society. Language choice gives the impact on marketing success and the perceptions of consumers towards the commercial products. It can influence cultural identity revealing the expression of cultural beliefs or core symbols deriving from the style of dress, labels, norms, and behaviours of especially the females. Thus, this study investigated concerning the following research questions: (1) How the female language choices reflected in the digital advertisement, (2) how does female cultural identity reflected in a digital advertisement. The objectives were to extent female language choices reflected in the digital advertisement and to extend female language choices reflected in digital advertisements. Method used in this study was desk research method. The data collected was advertisement selected from January to December 2022 through Youtube channel. The requirements to select the advertisements are as follows: (1) the digital advertisement promotes the beauty products that need to have women being linguistically portrayed in advertisements, (2) the Advertisement uses pictures without words excluded, and (3) the digital advertisements are well known by the customers in Indonesia context, (4) the content of digital advertisements reflects female's identity in Indonesia. The advertisements were selected as follows: (1) Dove, (2) Ms Glow Cream, (3) Wardah Cosmetics, and (5) Lux Botanical Body Wash. Language choice plays important role in advertisements. The language choice is taken into consideration to emphasize the effectiveness of the product that can persuade the female customers to be interactive to be beautiful or have positive characteristics that reflect the female’s identity in the information delivered. Moreover, the females represented their values and their identity as potential, talent, expression, characteristics, brave, and beauty that represent their values and their identity.